Hyperactivity of the sympatho-adrenomedullary system without any modification of the hypothalamic-pituitary-adrenal axis after food restriction among high-level weightlifters - Durguerian, A.; Filaire, E.; Drogou, C.; Sauvet, F.; Bougard, C.; Chennaoui, M. (The Journal of Strength and Conditioning Research, 2018)
We examined the effects of 6 days of food restriction on salivary a-amylase (sAA), cortisol and dehydroepiandrostenedione (DHEA) awakening responses, psychological parameters and performance among 11 international weightlifters. Assessments were made at baseline (T1) and 6 days after a normal period of training while maintaining body weight (T2). Then, participants were assigned to 2 groups depending on whether they lost (Diet group) or maintained (Control group) their body mass. Anthropometric, psychological, physical, and physiological assessments were also realized 6 days (T3) after the restricted dietary period for the Diet group. Food restriction (T3) induced a significant rise of sAA awakening response (364.6%, p = 0.05), whereas no significant variations were observed among the hypothalamic-pituitary-adrenal axis (cortisol and DHEA). Significant alterations of the general Recovery Score and General stress Score, evaluated through the Recovery-Stress Questionnaire for athletes, were noted after food restriction. Weightlifting performance, evaluated during a simulated weightlifting competition, was maintained after the 6-day food restriction; we even noted an increased weightlifting performance related to body mass (Sinclair coefficient). Our findings support the hypothesis that food restriction induces a challenging situation to the organism, resulting in an asymmetry between the 2 stress systems activation. These results reinforce the necessity to cautiously plan and monitor the weight regulation process before competition to avoid potential negative outcomes on psychophysiological parameters. In this regard, the psychobiological approach, especially the awakening responses, seems a useful tool.